The impacts of the coronavirus pandemic on the mental health of Brazilian diagnosed with COVID-19 and comparison of symptoms of depression, anxiety, insomnia, and post-traumatic stress with undiagnosed subjects - Silva, Sumayla Gabrielle Nascimento da; Carvalho, Lucas Mendes; Braga, Fernando Cesar de Souza; Silveira, Rodrigo; Santos, Ozélia Sousa (Frontiers in Psychiatry, 2023)
Background: The impacts of the COVID-19 pandemic on the mental health of survivors are little known, especially regarding the occurrence of psychological disorders such as anxiety and depression. In this study, we evaluated the impacts on the mental health of Brazilian survivors who were not infected or asymptomatic with COVID-19. Methods: A cross-sectional study was conducted collecting information through an electronic form from January to May 2021. The sample consisted of 1334 people and were divided into two groups: case, with individuals who reported a positive diagnosis of the disease, with or without symptoms, and control, who reported not being diagnosed with COVID-19 and did not present any symptoms during the collection period. Validated instruments were used to investigate symptoms of depression (Patient Health Questionnaire), anxiety (Generalized Anxiety Disorder-7), post-traumatic stress disorder (Post Traumatic Stress Disorder Checklist) and insomnia (Insomnia Severity Index). The data were presented as standard deviation or median and interquartile ranges. The chi-square test was applied for statistical significance between categorical variables, considering a p-value <0.05. Results: Regarding post-traumatic stress levels, the case and control groups showed no differences (p = 0.82). The results of the research indicated that was no statistical correlation between the group that was affected by the virus infection and the group that was not affected in terms of depression (p = 0.9) and anxiety (p = 0.7). At the same time, the levels of insomnia (p = 0.02) demonstrated a statistical correlation between the groups. The prevalence of the analyzed mental health disorders was similar among both groups. Conclusion: In conclusion, the population of survivors of COVID-19 infection tends to show little difference in terms of developing post-traumatic stress disorder, anxiety, and depression when compared to uninfected individuals. On the other hand, disorders such as insomnia are more prevalent and show a significant difference between groups, appearing more in infected individuals.